QUALITY DIMENSIONS OF ELEMENTARY EDUCATION UNDER RTE ACT 2009 - REKHA, CHITER (THE PRIMARY TEACHER, 2012)
Education is the backbone of a nation. The aim of education is expected to reflect the current needs and aspirations of a society as well as its lasting values. The aim of education serves as broad guidelines to align educational process to choose ideal and accepted principles. We would need to ensure that the aim of education is reflected in curriculum, syllabus, textbooks and other learning materials developed by us. Therefore an intelligent society will always invest in quality education for its children and youth. According to Dr Sarvepalli Radhakrishanan, the aim of education is not acquisition of information although important or acquisition of technical skills, though essential in modern society, but the development of that bent of mind, that attitude of reason, that sprit of democracy which make us responsible citizens. Mahatma Gandhi expressed that true education is the one that draws out and stimulates the spiritual, intellectual and physical facilities of children; he felt that craft or any other productive work could be the best medium of education. Apart from making education relevant to society, it should resulted in all round development of a child’s personality. In Gandhiji’s scheme, relevance was an important attribute of the quality of education.